Leadership in Action: Leading Change: Adapting and Innovating in an Uncertain World - Yukl, Gary; Lepsinger, Richard (Center for Creative Leadership, 2006)
In today's turbulent business environment, being able to respond in a timely way to emerging threats and opportunities is crucial to an organization's survival and prosperity. An organization's effectiveness can be improved by leader decisions that facilitate innovation and adaptation.